Hipoclorito e clorito de sódio: comparação de estabilidade de cloro livre - Costa, Cléber Duarte da (Universidade Federal de São Carlos, 2021)
The use of products based on available chlorine is common in industrial and household activities, which are generally strong related to purposes of fiber bleaching and disinfection. It is common to find the term active chlorine (available chlorine) written on these brazilian product labels referring to the active concentration and to inform about the product oxidizing feature. Available chlorine is the term used to refer to a unit of oxidizing capacity of chlorinated products which is used to estimate the concentration of chlorine-releasing compounds through its equivalent available chlorine. Sodium hypochlorite is a chlorine-releasing compound widely applied, also recognized by Brazilian Sanitary Surveillance Agency (ANVISA) and is present in several product compositions as chlorinated bleach and disinfectants. However, chlorine-releasing compounds in aqueous solution may have natural instability in terms of oxidizing capacity, which is related to degradability. The degradability of aqueous chlorine-releasing compounds is influenced by some factors and therefore it may reflect the available chlorine instability and in consequence chlorine-releasing compound based solutions may have decreasing disinfection and bleaching power over time. In context, this study sought to compare some ordinary formulation variations of bleach based on sodium hypochlorite and sodium chlorite as an available chlorine-releasing compound; in terms of available chlorine stability through weekly iodometric determination along the test period. According to the test results, conditioning the samples in 30ºC for 84 days, formulations with sodium chlorite were more stable when compared to those with hypochlorite showing no degradability in certain formulation compositions. Therefore, it is concluded that formulations with sodium chlorite may have greater available chlorine stability than those with sodium hypochlorite depending on the other components used in the formulation.
Hypochlorite and sodium chlorite: comparison of free chlorine stability
Keywords: Cloro livre; Hipoclorito de sódio; Clorito de Sódio; Alvejante; Desinfetante; Available chlorine; Sodium hypochlorite; Sodium Chlorite; Bleach; Disinfectant; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL